2017
DOI: 10.1002/bmc.4124
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive HPLC–MS/MS method for the simultaneous determination of anemoside B4, anemoside A3 and 23‐hydroxybetulinic acid: Application to the pharmacokinetics and liver distribution of Pulsatilla chinensis saponins

Abstract: Pulsatilla chinensis saponins, the major active components in the herb, have drawn great attention as potential hepatitis B virus infection and hepatoma treatments. Here, a sensitive and accurate HPLC-MS/MS method was established for simultaneous determination of three saponins - anemoside B4, anemoside A3 and 23-hydroxybetulinic acid - in rat plasma and liver, and fully validated. The method was successfully applied to a pharmacokinetics and liver distribution study of P. chinensis saponins. Consequently, 23-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Saikosaponin B4 had the highest initial concentration in the herbal medicine, followed by Hederagenin, which has relatively limited exposure. The hepatic first-pass effect was 23% for 23-hydroxybetulinic acid, 27% for saikosaponin B4, and 3% for Hederagenin, reflecting their varying degrees of hepatic distribution ( Guo et al, 2018 ).…”
Section: Pharmacokinetics Of Saponinsmentioning
confidence: 99%
“…Saikosaponin B4 had the highest initial concentration in the herbal medicine, followed by Hederagenin, which has relatively limited exposure. The hepatic first-pass effect was 23% for 23-hydroxybetulinic acid, 27% for saikosaponin B4, and 3% for Hederagenin, reflecting their varying degrees of hepatic distribution ( Guo et al, 2018 ).…”
Section: Pharmacokinetics Of Saponinsmentioning
confidence: 99%
“…The terpenoid and monomers in P. chinensis are widely adapted to clinical and veterinary treatment for their anticancer activity (Kang et al, 2019;Huihui Song et al, 2021). Pulsatilla saponins B3, BD, B4, B7, B9, B10, B11, A3, D, PSA, R13 and other components have been widely reported for their significant pharmacological activities (Xu et al, 2013;Liu, 2014;Liang, 2016;Guo et al, 2018;Yingying Luo et al, 2018;Kang et al, 2019;Yaru Cui et al, 2019;Zhang et al, 2021). Yingying Luo isolated and identified the total saponins of P. chinensis and the isolated monomers to study anti-tumor activity in vitro, and found that monomers of B3, B7, B9 and B11 could significantly inhibit tumor proliferation (Luo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The high content of B4 in the saponins has been used as a quality control marker for pulsatilla. The previous studies of B4 mainly focused on its composition identification, biotransformation, and tissue distribution [ 1 , 2 , 3 , 4 ]. The updated study in recent years reported that B4 has anti-inflammatory, immunomodulatory, antiapoptosis, and autophagy-enhancement effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%